2011
DOI: 10.1371/journal.pone.0027730
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Nickel, Chromium, or Cadmium Causes Distinct Changes in the Gene Expression Patterns of a Rat Liver Derived Cell Line

Abstract: Many heavy metals, including nickel (Ni), cadmium (Cd), and chromium (Cr) are toxic industrial chemicals with an exposure risk in both occupational and environmental settings that may cause harmful outcomes. While these substances are known to produce adverse health effects leading to disease or health problems, the detailed mechanisms remain unclear. To elucidate the processes involved in the toxicity of nickel, cadmium, and chromium at the molecular level and to perform a comparative analysis, H4-II-E-C3 rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 69 publications
2
48
0
Order By: Relevance
“…WNF 97-2-1 dissolves more slowly, at least from pellets (Schuster et al, 2012), produces only small quantities of reactive oxygen species compared to WNC 91-6-3, (Harris et al, 2011) and results in relatively few gene expression changes in HSkMC cells. As nickel can also alter expression of many of the genes affected by cobalt, for example HMOX1 and VEGFA (Permenter et al, 2011;Steinbrech et al, 2000), alloy formulations that dissolve to form higher local concentrations of nickel may also have greater effects, though to test this would require analysis of a range of different alloy formulations. Overall the results from the HSkMC cells agree with those from L6-C11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…WNF 97-2-1 dissolves more slowly, at least from pellets (Schuster et al, 2012), produces only small quantities of reactive oxygen species compared to WNC 91-6-3, (Harris et al, 2011) and results in relatively few gene expression changes in HSkMC cells. As nickel can also alter expression of many of the genes affected by cobalt, for example HMOX1 and VEGFA (Permenter et al, 2011;Steinbrech et al, 2000), alloy formulations that dissolve to form higher local concentrations of nickel may also have greater effects, though to test this would require analysis of a range of different alloy formulations. Overall the results from the HSkMC cells agree with those from L6-C11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The primer sequences were as follows: p16 5′-GGCACCAGAGGCAGTAACCA-3′ (forward) and 5′-CCTACGCATGCCTGCTTCTACA-3′, (reverse), CDK6 5′-GTGACCAGCAGCGGACAAATAA-3′ (forward) and 5′-AGCAAGACTTCGGGTGCTCTGTA-3′ (reverse), CDK4 5′-TTCTGCAGTCCACATATGCAACA-3′ (forward) and 5′- GGTCGGCTTCAGAGTTTCCAC -3′ (reverse), and GAPDH 5′- GAAGGTGAAGGTCGGAGTC -3′ (forward) and 5′- GAAGATGGTGATGGGATTTC -3′ (reverse). Relative fold change was determined using the comparative C t method using GAPDH as endogenous control [16].…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress and ER stress have become the important subjects in mammalian toxicology, and some non-essential heavy metals may be directly involved in these processes (Guo et al, 2009;Cao et al, 2013). Supporting this idea, some published data suggested that the exposure to metals could generate reactive oxygen species (ROS), causing the oxidative stress or ER stress in different tested models (Permenter et al 2011;Wang et al, 2013;Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 98%